The delay of contrast arrival in magnetic resonance first‐pass perfusion imaging: a novel non‐invasive parameter detecting collateral‐dependent myocardium - Muehling, O M (BMJ Group, 2007)
AIM: To establish the regional delay of contrast arrival in magnetic resonance perfusion imaging (MRPI) for the detection of collateral‐dependent myocardium in patients with coronary artery disease. DESIGN AND SETTING: Observational study, case series; single centre, university hospital. PATIENTS: 30 patients with coronary artery disease and collateral‐dependent myocardium and 17 healthy volunteers. METHODS: Resting and hyperaemic (adenosine) MRPI was used to determine the delay time (Δt(d)) of contrast arrival between the left ventricle and collateral‐dependent or antegradely perfused myocardium, and myocardial perfusion (MP, ml/min/g). RESULTS: In healthy volunteers, mean (SD) Δt(d) at rest and during hyperaemia were 0.8 (0.4) and 0.3 (0.3) s, and MP was 1.14 (0.21) and 4.23 (1.12) ml/min/g. In patients Δt(d) in antegradely perfused vs collateral‐dependent myocardium was 0.9 (0.7) vs 1.7 (1.0) s at rest (p<0.001), and 0.4 (0.3) vs 1.1 (0.6) s (p<0.001) during hyperaemia. MP was 1.12 (0.11) and 0.98 (0.28) ml/min/g (p = NS) at rest and 2.46 (0.85) vs 1.86 (0.91) ml/min/g (p<0.01) during hyperaemia. Receiver operating characteristics analysis showed the best sensitivity and specificity of 90% and 83% for hyperaemic Δt(d) of >0.6 s (area under the curve (AUC) = 0.89) to detect collateral‐dependent myocardium, while resting Δt(d) (AUC = 0.77) and perfusion (AUC = 0.69 at rest or 0.70 during hyperaemia) were less accurate. CONCLUSIONS: MRPI‐derived hyperaemic delay of contrast arrival detects collateral‐dependent myocardium with high sensitivity and specificity. Perfusion was less sensitive, emphasising the clinical role of Δt(d) in non‐invasive detection of collateral‐dependent myocardium.